A Study on Authentication Issues in Cloud Computing Environment - Kumbhakar, Dulal; Karforma, Sunil (International Journal of Computer Sciences and Engineering, 2025)
Cloud computing is the new emerging technology and its real trends toward massively scalable various computing services. Cloud computing services are used widely to foster the business volume of an organization or industry based on delivery and consumption of everything from storage to computing management services with minimum effort. Regarding to this importance, the service providers of this technology needs to address many issues related to the cloud computing environment security issues like privacy, authentication and integrity issues etc. Many researchers worked on these issues and provide the possible mechanisms to resolve the issues. However our paper represents a critical study on authentication issues in cloud computing environment.